Tweety-homolog (Ttyh) Family Encodes the Pore-forming Subunits of the Swelling-dependent Volume-regulated Anion Channel (VRAC(swell)) in the Brain - Han, Young-Eun; Kwon, Jea; Won, Joungha; An, Heeyoung; Jang, Minwoo Wendy; Woo, Junsung; Lee, Je Sun; Park, Min Gu; Yoon, Bo-Eun; Lee, Seung Eun; Hwang, Eun Mi; Jung, Jae-Young; et al. (KOREAN SOC BRAIN & NEURAL SCIENCE, KOREAN SOC NEURODEGENERATIVE DISEASE, 2019)
In the brain, a reduction in extracellular osmolality causes water-influx and swelling, which subsequently triggers Cl - and osmolytes-efflux via volume-regulated anion channel (VRAC). Although LRRC8 family has been recently proposed as the pore-forming VRAC which is activated by low cytoplasmic ionic strength but not by swelling, the molecular identity of the pore-forming swelling-dependent VRAC (VRAC(swell)) remains unclear. Here we identify and characterize. Tweety- homologs (TTYH1, TTYH2, TTYH3) as the major VRAC(swell) in astrocytes. Gene-silencing of all Ttyh1/2/3 eliminated hypo-osmotic-solution-induced Cl- conductance (I-Cl,I-swell) in cultured and hippocainpal astrocytes. When heterologously expressed in HEK293T or CHO-K1 cells, each TTYH iso-form showed a significant I-Cl,I-swell with similar aquaporin-4 dependency, pharmacological properties and glutamate permeability as I-Cl,I-swell observed in native astrocres. Mutagenesis-based structure-activity analysis revealed that positively charged arginine residue at 165 in TTYH1 and 164 in TTYH2 is critical for the formation of the channel-pore. Our results demonstrate that TTYH family confers the bona fide VRAC(swell) in the brain.
Keywords: SENSITIVE CL-CHANNEL; CHLORIDE CURRENTS; GLUTAMATE RELEASE; ESSENTIAL COMPONENT; ASTROCYTES; ROLES; PROTEIN; IDENTIFICATION; CONDUCTANCE; EXPRESSION